Analyzing the Impact of Subsidies on Beef Production Efficiency in Selected European Union Countries. A Stochastic Metafrontier Approach. Issue 5 (5th April 2021) - Martinez Cillero, Maria; Wallace, Michael; Thorne, Fiona; Breen, James
Abstract : The European Union Common Agricultural Policy reforms since the early 2000s allowed for the implementation of different types of agricultural subsidies, such as direct support in the form of decoupled and coupled payments, or agri‐environmental payments. As a result, there are significant differences in agricultural subsidies granted in each member state of the European Union. However, there is limited cross‐country comparative empirical evidence regarding the effects of the implementation of different levels and types of subsidies on farm efficiency. Using farm level data for beef farms in Ireland, France, Great Britain, and Germany between 2005 and 2012, we implement the stochastic metafrontier proposed by Huang et al. (2014) and attempt to correct for endogeneity applying the method in Shee and Stefanou (2015). Using these approaches, we contribute to the literature by consistently comparing cross‐country farm performance, as well as exploring the disaggregated effects of different types of subsidies on farm level technical efficiency and on the technology gaps. Our estimates show that although beef farms included operate on average close to the global frontier, there is scope to improve farm level managerial performance. However, they do operate close to the global frontier, although not on it. We also find evidence that implementing full decoupling benefited efficiency, whereas implementing partial decoupling might have hindered technical efficiency improvements for beef farms, as well as technology catch up.